Kingdoms in conflict - Colson, Charles; Vaughn, Ellen Santilli ([New York] : W. Morrow ; [Grand Rapids, MI] : Zondervan Pub. House, 1987)
"An insider's challenging view of politics, power, and the pulpit"--Jacket subtitle.
Part one: need for the kingdom -- 1. Kingdoms in conflict -- 2. After the feast -- 3. Crossing the rubicon -- 4. Faith and the evidence -- 5. Neither ape nor angel -- Part two: arrival of the kingdom -- 6. King without a country -- 7. Politics of the kingdom -- 8. For the good of the nations -- 9. The cross and the crown -- Part three: absence of the kingdom -- 10. Roots of war (part one) -- 11. Roots of war (part two) -- 12. Year zero -- 13. Marxism and the kingdom of God -- 14. Conflict and compromise in the west -- 15. The naked public square -- Part four: presence of the kingdom -- 16. Benefits of the kingdom -- 17. Christian patriotism -- 18. Little platoons -- 19. The problem of power -- 20. Christians in politics -- 21. Signs of the kingdom -- 22. Perils of politics -- 23. People power -- 24. The political illusion -- 25. The indestructible kingdom.
"A Judith Markham book."
Includes bibliographical references (pages 390-391) and index.
Keywords: Christianity and politics; Church and state